Reception and enactment of the compulsory secondary education reform. Stephen Ball's contributions to the study of educational policies in schools of Santa Cruz province, Argentina - María Cecilia Bocchio; Silvia Mariela Grinberg; Carla Andrea Villagran (Arizona State University, 2016)
This paper presents key progress in a research based in Stephen Ball's work, specifically the contributions that relate to policy trajectories analysis or the Policy Cycle approach. Specifically, we focus in the enactment context, in which the reform policies of compulsory secondary education are received and enacted in two public secondary schools, located in the city of Caleta Olivia, Santa Cruz. We develop three analytical dimensions, seeking to understand how subjects experience educational reform policies in secondary education. These dimensions are: 1. The abrupt character of the reform; 2. Reform's institutional communication 3. Rhetoric of participation and commitment in times of hyper bureaucracy and management. This paper highlights some of Ball's major contributions to research the educational policy enactment process in "real schools" of Argentina.